Contract Doctrine, Theory & Practice Volume 1 - Verkerke, J.H.; Open Textbook Library (Open Textbook Library, 2012)
This is the first in a series of Contracts casebooks. It was originally titled "Collaborative Teaching Materials for Contracts." The first semester of law school is mostly about learning to speak a new legal language (but emphatically not "legalese"), to formulate and evaluate legal arguments, to become comfortable with the distinctive style of legal analysis. We could teach these skills using almost any legal topic. But we begin the first-year curriculum with subjects that pervade the entire field of law. Contract principles have a long history and they form a significant part of the way that lawyers think about many legal problems. As you will discover when you study insurance law, employment law, family law, and dozens of other practice areas, your knowledge of contract doctrine and theory will be invaluable.
I. Introduction to the Legal Significance of Promise Making -- 1. What is a Promise? -- 2. Which Promises Are Enforced? -- II. The Consideration Requirement and Alternatives -- 1. Consideration Doctrine -- 2. Bargain or Gift? -- 3. Adequacy Doctrine -- 4. Promissory Estoppel -- 5. The Material Benefit Rule -- III. Contract Formation -- 1. Offer -- 2. Acceptance -- 3. Revocation of Offers -- 4. UCC Section 2-207 -- 5. Frontiers of Contract Formation
In English.
Description based on print resource
Keywords: Business -- Textbooks; Law -- Textbooks -- United States; Contract Law -- Textbooks